Productivity of bananas (MusaAAA) grown in Urabá, Carepa, department Antioquia - González-Pedraza, Ana Francisca; Romero Delgado, Raúl Andrés; Maestre Delgado, Marisol (Ingeniería Solidaria, 2025)
Introduction: Bananas are in high demand worldwide and play a vital role in the economies of several tropical countries. Colombia ranks as the ninth-largest banana producer globally, with Carepa, located in the Urabá region of Antioquia, serving as the nation’s leading producer and exporter. The region’s diverse soil types and agricultural practices significantly impact the quality and yield of banana crops. This project was conducted in 2021 with the support of the University of Pamplona.Objective: To determine the relationship between banana productivity and the level of soil compaction by evaluating plant vigor parameters and physical soil characteristics on three farms in Urabá.Methodology: On three farms, productivity parameters were measured for plants with high vigor (HV) and low vigor (LV): circumference of the pseudostem of the mother plant (CPP), height of the young sword sucker (HSS), number of hands per bunch (NHB), number of fingers per hand (NFH), length of the middle finger (LMF), and diameter of the middle finger (DMF). Soil bulk density (SBD), texture, and other physical properties were also assessed.Results: CPP, HSS, and NHB were statistically higher (p < 0.05) in HV plants compared to LV plants. For NFH and LMF, no significant differences were observed between HV and LV plants at the Velero and Fragata farms (p > 0.05), while at the Piragua farm, HV plants exhibited significantly greater NFH and LMF.Conclusion: Soil compaction has a direct effect on banana productivity. Adverse effects were noted at the Fragata farm, which exhibited lower yields and bunch weight compared to the other farms.Originality: This study uniquely correlates soil compaction with banana productivity within an agricultural context in Colombia.Limitations: The study was limited to three farms, so it is recommended to extend the analysis to additional locations for more generalized results.